A Challenging Case of Severe Ulcerative Colitis following the Initiation of Secukinumab for Ankylosing Spondylitis. (15th February 2018) - Ehrlich, Dean; Jamaluddin, Nimah; Pisegna, Joseph; Padua, David
Abstract : Secukinumab is an interleukin-17 inhibitor used for the treatment of ankylosing spondylitis (AS), psoriasis, and psoriatic arthritis. The risk of exacerbating underlying inflammatory bowel disease (IBD) in patients being treated with secukinumab for other conditions is controversial. We document a patient with AS and previously undiagnosed IBD, found to be in a severe ulcerative colitis flare shortly after receiving the loading dose of secukinumab. There are no guidelines regarding biologic salvage therapy for IBD in the setting of active treatment with another biologic agent. After waiting one half-life of secukinumab, our patient had an excellent response to initiation of infliximab.